2018
DOI: 10.1111/mpp.12763
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the cold shock protein CspA to virulence in Xanthomonas oryzae pv. oryzae

Abstract: Summary Xanthomonas oryzae pv. oryzae ( Xoo ) causes a damaging bacterial leaf blight disease in rice. Cold shock proteins (Csps) are highly conserved nucleic acid‐binding proteins present in various bacterial genera, but relatively little is known about their functions in Xanthomonas . Herein, we identified four Csps (CspA–CspD) in the Xoo PXO99 A strain. Deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Bacterial Csp homologs are involved in a wide range of functions including cold tolerance, general stress response, and virulence (12,17,23). Csps involved in both stress response and virulence have been found in many animal pathogens such as L. monocytogenes (16,19), Brucella melitensis (24), Salmonella enterica serovar Typhimurium (14), Enterococcus fecalis (23), Staphylococcus aureus (25), as well as plant pathogens Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacterial Csp homologs are involved in a wide range of functions including cold tolerance, general stress response, and virulence (12,17,23). Csps involved in both stress response and virulence have been found in many animal pathogens such as L. monocytogenes (16,19), Brucella melitensis (24), Salmonella enterica serovar Typhimurium (14), Enterococcus fecalis (23), Staphylococcus aureus (25), as well as plant pathogens Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Csps involved in both stress response and virulence have been found in many animal pathogens such as L. monocytogenes (16,19), Brucella melitensis (24), Salmonella enterica serovar Typhimurium (14), Enterococcus fecalis (23), Staphylococcus aureus (25), as well as plant pathogens Xanthomonas oryzae pv. oryzae (17) and X. fastidiosa (12). Deleting Csp genes in these bacteria resulted in attenuated virulence, sometimes together with changes to cellular aggregation, surface attachment, and biofilm formation (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CSP was identified from bacteria as a PAMP in tobacco [ 73 ]. CSP was identified from Xoo as important for virulence against rice [ 81 ]. In the present study, two CSP proteins from Escherichia and Buchnera were identified in both BPH and GRH honeydews.…”
Section: Discussionmentioning
confidence: 99%